While Europe slept: how radical Islam is destroying the West from within - Bawer, Bruce (Doubleday, 2006)
Before 9/11: Europe in denial -- 9/11 and after: blaming Americans and Jews -- Europe's Weimar moment: the liberal resistance and its prospects